The Construction of Religious Moderation among Indonesian Muslim Academics - Zulkifli, Zulkifli; Kafid, Nur; Nanang, Herlino; Fahri, Muhamad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2023)
Despite the popular recognition of Indonesian Islam as being accommodative and moderate, there is a more conservative trend noticeable in the social and political sphere. Alerted by this recent development, the Ministry of Religious Affairs formulated the policy of religious moderation, which has drawn the attention of academicians. This research aims to gauge the level of religious moderation among lecturers of State Islamic Higher Education Institutions in Indonesia and its contributing factors. Specifically, this study attempts to examine whether variables of interreligious interaction, university policy, and socio-cultural context significantly influence the construction of religious moderation. It used a mixed method of quantitative and qualitative approaches with convergent parallel design. The quantitative approach applied a survey method using a questionnaire involving 272 lecturers at twelve institutions selected through multistage systematic sampling, while the qualitative approach used a focus group discussion technique to the management of the Religious Moderation House in 10 universities. The research revealed that the average level of religious moderation is moderate. The variables that significantly influenced religious moderation were university policies and sociocultural context, while the interreligious interaction variable had no significant effect. More complex variables need to be considered in future research.